JAPANESE EXPERIENCE ISSUES OF MODERN MANAGEMENT AND PERSONNEL RE-TRAINING SYSTEM - Dadajanova Martaboxon Mahmudovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In the article, an example of national features of retraining and management of enterprises’ personnel is analyzed on the example of Japanese management. The opportunities of this advanced experience implementation in the national economy are discussed.